Effects of land use patterns on soil physical and thermal properties in basement complex and sedimentary areas of Ogun State, Nigeria - Saheed Adekunle Ganiyu; Taiye Ayuba Ishola; Oluwaseun Tolutope Olurin; Biodun Suraj Badmus; Mutiu Abolanle Busari (Discover Geoscience)
Abstract Understanding the soil thermal properties (STPs) are essential for managing soil thermal regions under different land uses patterns. Therefore, this study focused on measuring field STPs and the physical properties of soils across different land use patterns (football pitch (FP), abattoir site (AS), dumpsite (DS), and cement brick making (BM) in basement complex (Odeda) and cretaceous sedimentary formation (Sagamu) in Ogun State, Nigeria. Thermal properties were measured in situ using KD2 Pro Thermal Properties Analyzer while soil physical parameters were determined using standard laboratory techniques. The results revealed that the highest mean thermal conductivity $${(λ }_{s}$$ ( λ s ) values observed in the basement and sedimentary formations were 1.53 and 1.98 W/mK, recorded in DS and FP, respectively. In terms of specific heat capacity (CS), the maximum and minimum mean values of 3.93 and 1.49 MJ/mK were recorded in DS and BM within the basement complex lithology. Additionally, the highest and lowest thermal admittance ( $${μ }_{s}$$ μ s ) values of 3.36 and 1.71 mm2/s, along with soil moisture contents (MC) of 51.08% and 26.28%, were observed in FP and BM, respectively, within the basement complex area. However, the sedimentary area exhibited the opposite trend. The mean thermal resistivity (TR) values for FP, AS and BM in the sedimentary formation, as well as for DS in the basement complex, were within the recommended threshold (90 °C cm/W) for safe telecommunication signals and positioning of oil and gas conduits. The regression models revealed that the double-log model outperformed both the pair linear and semi-log models for predicting $${λ }_{s}$$ λ s at the two geological formations, achieving an R2 value of 100% and significant F-values. The results revealed that nearly all the soil thermal characteristics were, significantly influenced by lithology and land management practices. The findings of this study will assist land users to make best choice of appropriate land management practices for sustainable agriculture and environmental preservation.